2020
DOI: 10.3390/s20164405
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Microsoft Kinect V2 Sensor for Human Gait Analysis. A Different Approach for Comparison with the Ground Truth

Abstract: Several studies have examined the accuracy of the Kinect V2 sensor during gait analysis. Usually the data retrieved by the Kinect V2 sensor are compared with the ground truth of certified systems using a Euclidean comparison. Due to the Kinect V2 sensor latency, the application of a uniform temporal alignment is not adequate to compare the signals. On that basis, the purpose of this study was to explore the abilities of the dynamic time warping (DTW) algorithm to compensate for sensor latency (3 samples or 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Regarding the hardware and software, the mechanism of posture recognition is based on projecting a pulsed infrared pattern and simultaneously measuring the reflection with an infrared sensor and a red/green/black (RGB) sensor. Kinect measures the time of flight (TOF) for each pattern and then matches the data to the RGB image [ 16 ]. Our preliminary study showed that the detection of heel strike judged from the position of the ankle was not precisely recognized because infrared was blocked in the case where the forefoot covers the ankle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the hardware and software, the mechanism of posture recognition is based on projecting a pulsed infrared pattern and simultaneously measuring the reflection with an infrared sensor and a red/green/black (RGB) sensor. Kinect measures the time of flight (TOF) for each pattern and then matches the data to the RGB image [ 16 ]. Our preliminary study showed that the detection of heel strike judged from the position of the ankle was not precisely recognized because infrared was blocked in the case where the forefoot covers the ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to recognize exact ankle detection, we adopted a hip-knee cyclogram in this study [ 12 ]. As for the number of Kinect installed for gait analysis, multiple Kinect systems have been used for gait analysis [ 8 , 16 ] ( Table 5 ). However, the use of multiple Kinect systems requires relatively high cost and technical skills to integrate each data.…”
Section: Discussionmentioning
confidence: 99%
“…Latency compensation allows for the suppression of time delays due to data processing time in 3D cameras. In our previous study [18], the latency of the Kinect V2 sensor was measured and corrected using the Dynamic Time Warping (DTW) algorithm. The latency compensation process improves the estimation of joint angles during gait analysis.…”
Section: State Of the Artmentioning
confidence: 99%
“…All patients in the experimental and control groups had their spatio-temporal gait parameters evaluated at baseline, four and eight weeks after the intervention. Spatio-temporal gait parameters were identified by using a markless 3D motion analysis sensor, the Microsoft Kinect V2 [20]. Each patient was asked to walk toward the Kinect sensor (Microsoft Kinect™ V2) maintaining a comfortable speed without being instructed to correct their gait.…”
Section: • Marching In Placementioning
confidence: 99%